Cartografia de um processo de coterapia sob um olhar fonoaudiológico - Ferraz, Silvia Daniella Guedes (2012)
The advance of clinical researches and experiences in treating children with disabilities points to the need of development of therapeutic projects which promote the integration of different professional views on the cases. From clinical experiences and reflections the cotherapy was thought, in the present research, as a device to serve this population through the joint action of speech therapy, physiotherapy and occupational therapy. The purpose of this investigation was to map such cotherapy experiences in order to analyze potential and limits of this device. To this end, we carried out the mapping and analysis of the clinical trials proposed in two cases: a seven-year-old with Down syndrome, and another four-year old one with cerebral palsy. The cartography was constructed from actual experiences with patients, scores made by their parents, and perceptions recorded by the professionals involved in the experiment. These processes of cotherapy have been well evaluated by the families as well as the patients. Some conditions of possibility were highlighted on them: the care and attention to the setting which this type of meeting requires and produce; multiple and singular composition of the therapeutic relationships, and articulation among the therapists. Considering the need for training of professionals and the care in the management of the work processes, the cotherapy proved to be an effective tool in the treatment of disabled children, promoting integrated vision, construction of more comprehensive clinical listening, and the elaboration of interdisciplinary singular therapeutic projects. It also collaborated with the expansion of capacity to meet the specific needs of each case investigated. It was also possible to note that the disciplinary backgrounds of the professionals had to be open to the reinvention of values and positions, based on how the knowledge of a discipline affected and was affected by the others. Taking into account and being submitted to such intersections this clinical practice can be considered inventive, creative